Synthesis and switching properties of new derivatives of azoresveratrol. (December 2019) - Berthet, Jérôme; Agouridas, Laurence; Chen, Siyao; Allouchi, Hassan; Melnyk, Patricia; Champagne, Benoît; Delbaere, Stéphanie
Abstract: The synthesis and response upon light irradiation of azoresveratrol and six derivatives are reported. While UV irradiation of para-hydroxy trans compounds leads to thermally unstable cis isomers, the para-methoxy and the para-phosphoric ester substituents result in reaching a high conversion and increasing the thermal stability. In addition, the phosphoric ester azo derivative presents similar properties in organic and aqueous solutions, opening the way towards biological applications. Graphical abstract: Image 1 Highlights: Photoswitching of azoresveratrol and six derivatives was studied by UV–Visible and NMR spectroscopies. Bi-exponential behaviour of the thermal relaxation was evidenced. DFT calculations were carried out to rationalize the experimental observations. The trans phosphoric ester azo derivative is water-soluble and highly photoconverted to its thermally stable cis isomer.